Good meat : the complete guide to sourcing and cooking sustainable meat - Krasner, Deborah (New York : Stewart, Tabori & Chang, 2010)
Good Meat is a cookbook entirely devoted to the cause of sustainably raised meat, with recipes, cooking tips, sources and cut sheets
1. Acknowledgements -- 2. Foreword -- 3. Introduction -- 4. Equipment -- 5. Ingredients -- 6. Beef -- 7. Lamb -- 8. Pork -- 9. Rabbit -- 10. Poultry -- 11. Eggs -- 12. Side dishes
With more than 200 recipes
Includes bibliographical references and index
Keywords: Cooking (Meat); Cooking (Poultry); Meat industry and trade -- Environmental aspects -- United States; Sustainable living -- United States